Is it all about territory? Israel's settlement policy in the occupied Palestinian territory since 1967 - Leila Stockmarr (Danish Institute for International Studies (DIIS), 2012)
Changing with rapid speed, the current political geography of the occupied Palestinian territory has de facto come to undermine a two-state solution and is turning the official aim and end point of international negotiations at best into a naive mirage for policymakers and at worst into a facade for a very different political game playing out in the occupied territory of the West Bank and Israeli-annexed East Jerusalem: that of Israel's ongoing territorial expansion into Palestinian land. The study shows how the settlement policies inside what are internationally-recognised Palestinian territories are not merely undermining the realisation of the two-state solution: the territorial claims put forward and pursued in practice and their anchoring in strategies of legitimisation reach far beyond international legal standards. This reveals a very different political narrative embedded at the core of the conflict from that projected by those images often appearing in the mainstream media and policy circles: a narrative of an ongoing struggle over land detached from any 'Peace Process' measures.
Keywords: 300